Решение тригонометрического уравнения

Erstellt am: 17. Januar 2025

Beantwortet mit O1 von Chat01

Frage

Решите уравнение $$\mathrm{sin}2x+\mathrm{cos}2x+\mathrm{sin}x+\mathrm{cos}x+1=0$$. 

Gedanke

Breaking down the equation

I’m using trigonometric identities to simplify the equation. Substituting sin(2x)\sin(2x) and cos(2x)\cos(2x), the equation becomes 2sinxcosx+(cos2xsin2x)+sinx+cosx+12 \sin x \cos x + (\cos^2 x - \sin^2 x) + \sin x + \cos x + 1.

Simplifying with identities

I’m using angle addition formulas to rewrite sin(2x)+cos(2x)\sin(2x) + \cos(2x) as 2sin(2x+π/4)\sqrt{2}\sin(2x + \pi/4) and sin(x)+cos(x)\sin(x) + \cos(x) as 2sin(x+π/4)\sqrt{2}\sin(x + \pi/4).

Transforming the equation

I’m using trigonometric identities to transform the equation into 22sin(3x2+π4)cos(x2)=12\sqrt{2} \sin\left(\frac{3x}{2} + \frac{\pi}{4}\right) \cos\left(\frac{x}{2}\right) = -1.

Rewriting and simplifying

I'm reworking the expression by defining u=sinx+cosxu = \sin x + \cos x and leveraging identity transformations to express the equation in terms of sinx+cosx\sin x + \cos x.

Formulating a new strategy

I’m mapping out strategies to express sin(2x)+cos(2x)\sin(2x) + \cos(2x) in terms of sinx+cosx\sin x + \cos x, such as defining new variables uu and vv.

Combining terms

I’m consolidating sin(2x+π/4)\sin(2x + \pi/4) and sin(x+π/4)\sin(x + \pi/4) using trigonometric identities, leading to sin(3x2+π4)cos(x2)=122\sin\left(\frac{3x}{2} + \frac{\pi}{4}\right) \cos\left(\frac{x}{2}\right) = -\frac{1}{2\sqrt{2}}.

Ensuring consistency

I’m mapping out the equation with sin(3x2+π4)cos(x2)\sin\left(\frac{3x}{2} + \frac{\pi}{4}\right) \cos\left(\frac{x}{2}\right) to verify it aligns with the original equation.

Refining the approach

I’m considering simplifying the equation by substituting u=sinx+cosxu = \sin x + \cos x. This method will help express everything in terms of uu.

Piecing together

I’m pulling together expressions for 2sinxcosx2 \sin x \cos x and cos2xsin2x\cos^2 x - \sin^2 x using uu and vv to find common terms and simplify the equation further.

Reworking identities

I’m re-examining the identity cos2xsin2x=cos(2x)\cos^2 x - \sin^2 x = \cos(2x) and expressing it through uu and vv to find common terms for further simplification.

Translating the equation

I’m translating the equation into terms of uu and vv to express sin(2x)+cos(2x)\sin(2x) + \cos(2x) as (u21)+uv(u^2 - 1) + uv, aiming for further simplification.

Piecing it together

I’ve figured out how to express u2+uv+u=0u^2 + uv + u = 0 and found v=±2u2v = \pm \sqrt{2 - u^2}.

Evaluating solutions

First, I’m setting u=0u = 0 and seeing if sinx+cosx=0\sin x + \cos x = 0 works. Then, I’m checking that against the original equation to confirm its validity.

Mapping out solutions

I’m figuring out two solution sets: x=π4+nπx = -\frac{\pi}{4} + n\pi and cosx=12\cos x = -\frac{1}{2} leading to x=±2π3+2kπx = \pm \frac{2\pi}{3} + 2k\pi.

Examining solution constraints

I’m verifying the solutions are consistent with the original equation, ensuring no constraints were overlooked, particularly for cosx=12\cos x = -\frac{1}{2}.

Verifying consistency

I’m making sure that cosx=12\cos x = -\frac{1}{2} and corresponding sinx\sin x values fit with the original equation, checking solutions like x=2π3+2kπx = \frac{2\pi}{3} + 2k\pi.

Ensuring solution clarity

I’m refining the solution set to x=π4+nπx = -\frac{\pi}{4} + n\pi and x=2π3+2nπx = \frac{2\pi}{3} + 2n\pi or x=4π3+2nπx = \frac{4\pi}{3} + 2n\pi for clarity.

Thought about solving trigonometric equation for 1m 23s

Antwort

Решение уравнения

sin(2x)  +  cos(2x)  +  sinx  +  cosx  +  1  =  0\sin(2x)\;+\;\cos(2x)\;+\;\sin x\;+\;\cos x\;+\;1\;=\;0

Шаг 1. Упрощение с помощью замен

Для удобства введём одну вспомогательную переменную

u  =  sinx  +  cosx.u \;=\;\sin x \;+\;\cos x.

Тогда:

  1. sinx+cosx=u.\sin x + \cos x = u.
  2. sin(2x)=2sinxcosx.\sin(2x) = 2\,\sin x\,\cos x.
  3. cos(2x)=cos2x    sin2x.\cos(2x) = \cos^2 x \;-\;\sin^2 x.

Обратим внимание, что

(sinx+cosx)2  =  sin2x+2sinxcosx+cos2x  =  1  +  2sinxcosx.(\sin x + \cos x)^2 \;=\;\sin^2 x + 2\,\sin x\,\cos x + \cos^2 x \;=\;1 \;+\; 2\,\sin x\,\cos x.

Отсюда

2sinxcosx  =  u2    1.2\,\sin x\,\cos x \;=\;u^2 \;-\;1.

Также

cos2xsin2x  =  (cosx+sinx)(cosxsinx).\cos^2 x - \sin^2 x \;=\;(\cos x + \sin x)\,(\cos x - \sin x).

Введём ещё

v  =  cosx    sinx.v \;=\;\cos x \;-\;\sin x.

Тогда произведение

(cosx+sinx)(cosxsinx)  =  uv.(\cos x + \sin x)\,(\cos x - \sin x) \;=\; u\,v.

Шаг 2. Выражение sin(2x)+cos(2x)\sin(2x) + \cos(2x) через uu и vv

Имеем

sin(2x)+cos(2x)  =  2sinxcosx  +  (cos2xsin2x)  =  (u21)2sinxcosx  +  (uv)cos2xsin2x.\sin(2x) + \cos(2x) \;=\; 2\,\sin x\,\cos x \;+\; (\cos^2 x - \sin^2 x) \;=\; \underbrace{(u^2 - 1)}_{2\,\sin x\,\cos x} \;+\; \underbrace{(u\,v)}_{\cos^2 x-\sin^2 x}.

Таким образом левая часть исходного уравнения

sin(2x)  +  cos(2x)  +  sinx  +  cosx  +  1\sin(2x)\;+\;\cos(2x)\;+\;\sin x\;+\;\cos x\;+\;1

превращается в

(u21)  +  uv  +  u  +  1.(u^2 - 1) \;+\; u\,v \;+\; u \;+\; 1.

Сгруппируем:

(u21)+1=u2,а также добавляется uv+u.(u^2 - 1) + 1 = u^2, \quad \text{а также добавляется }u\,v + u.

Итого получаем

u2  +  uv  +  u  =  0.u^2 \;+\; u\,v \;+\; u \;=\; 0.

Вынесем uu за скобку:

u(u+v+1)  =  0.u \bigl(u + v + 1\bigr) \;=\; 0.

Значит, либо

  1. u=0,u = 0,
  2. u+v+1=0.u + v + 1 = 0.

Рассмотрим эти случаи по отдельности.


Шаг 3. Случай u=0u = 0

u=sinx+cosx=0        sinx=cosx.u = \sin x + \cos x = 0 \;\;\Longrightarrow\;\; \sin x = -\,\cos x.

Поделив (где это допустимо) на cosx\cos x, получим

tanx=1.\tan x = -1.

Основное решение уравнения tanx=1\tan x = -1 есть

x=π4+nπ,nZ.x = -\tfrac{\pi}{4} + n\pi, \quad n \in \mathbb{Z}.

(Эквивалентно можно было бы записать x=3π4+nπx = \tfrac{3\pi}{4} + n\pi, это одно и то же семейство корней.)


Шаг 4. Случай u+v+1=0u + v + 1 = 0

u+v+1=0        (sinx+cosx)+(cosxsinx)+1=0.u + v + 1 = 0 \;\;\Longrightarrow\;\; (\sin x + \cos x) + (\cos x - \sin x) + 1 = 0.

Здесь sinx\sin x сократятся:

2cosx+1=0        cosx=12.2\,\cos x + 1 = 0 \;\;\Longrightarrow\;\; \cos x = -\,\tfrac12.

Решения уравнения cosx=12\cos x = -\tfrac12 на основной периоде 0x<2π0 \le x < 2\pi суть

x=2π3илиx=4π3.x = \tfrac{2\pi}{3} \quad\text{или}\quad x = \tfrac{4\pi}{3}.

С учётом периодичности косинуса (период 2π2\pi) общее решение:

x=2π3+2nπилиx=4π3+2nπ,nZ.x = \tfrac{2\pi}{3} + 2n\pi \quad\text{или}\quad x = \tfrac{4\pi}{3} + 2n\pi, \quad n \in \mathbb{Z}.

Итоговый ответ

Все решения исходного уравнения

sin(2x)  +  cos(2x)  +  sinx  +  cosx  +  1  =  0\sin(2x)\;+\;\cos(2x)\;+\;\sin x\;+\;\cos x\;+\;1\;=\;0

даются объединением следующих семейств:

  1. x=π4+nπ,nZ;\displaystyle x = -\tfrac{\pi}{4} + n\pi,\quad n\in \mathbb{Z};
  2. x=2π3+2nπ,nZ;\displaystyle x = \tfrac{2\pi}{3} + 2n\pi,\quad n\in \mathbb{Z};
  3. x=4π3+2nπ,nZ.\displaystyle x = \tfrac{4\pi}{3} + 2n\pi,\quad n\in \mathbb{Z}.

На практике их часто записывают в таком виде:

x  =  π4+nπилиx  =  2π3+2nπилиx  =  4π3+2nπ,nZ.\boxed{ x \;=\; -\tfrac{\pi}{4} + n\pi \quad\text{или}\quad x \;=\; \tfrac{2\pi}{3} + 2n\pi \quad\text{или}\quad x \;=\; \tfrac{4\pi}{3} + 2n\pi, \quad n\in\mathbb{Z}. }

Diesen Q&A teilen